Chemical Composition of Iran's Pistacia atlantica Cold-Pressed Oil - M. Saber-Tehrani; M. H. Givianrad; P. Aberoomand-Azar; S. Waqif-Husain; S. A. Jafari Mohammadi (Journal of Chemistry)
The lipid fraction of Pistacia atlantica seeds was extracted for the first time by means of cold-press technique and analyzed for its chemical composition. The fatty acids, sterols, triacylglycerols (TAG), tocopherols, polyphenols, and pigments were identified and their concentrations were determined by means of reversed-phase high-performance liquid chromatography (RP-HPLC) and gas chromatography (GC). Because of its high content of unsaturated fatty acids, it might prove to be of value in diets and it may be used as edible cooking or salad oils or for margarine manufacture. Pistacia atlantica seed oil has the unique sterols and tocopherols content providing source of natural antioxidants. The main triacylglycerols were SLL + PLO, SOL + POO, OOLn + PLL, OOO, and SOO. This paper examined the phenolic fraction of Pistacia atlantica seed oil. Moreover, caffeic acid followed by cinnamic acid, pinoresinol, vanillin, p-Coumaric acid, ferulic acid, and o-Coumaric acid was also determined. This paper presents the first investigation of chlorophyll's and carotene's composition in Pistacia atlantica seed oil. Furthermore, pheophytin a was the major component, followed by luteoxanthin, neoxanthin, violaxanthin, lutein, lutein isomers, chlorophyll a, chlorophyll a′, and pheophytin a′ were also determined.